2018
DOI: 10.1007/s12975-018-0672-5
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Epoxide Hydrolase-Derived Linoleic Acid Oxylipins in Serum Are Associated with Periventricular White Matter Hyperintensities and Vascular Cognitive Impairment

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science+Business Media, LLC, part of Springer Nature. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to selfarchive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 32 publications
3
35
3
Order By: Relevance
“…Frozen collections of serum and plasma from studies of neurocognitive disorders, including measures of cognitive function, provide a resource for biomarker discovery in this arena 22 However, opportunistically collected samples rarely contain information regarding fed/fasted states, which can compromise “omics” analyses. Here, we took advantage of data and biospecimens from subjects in the Religious Order Study and Rush Memory and Aging Project (ROS/MAP) 23 , develop a predictive tool for the fasted/non-fasted state discrimination and stratify our biomarker discovery effort by the fasted state.…”
Section: Introductionmentioning
confidence: 99%
“…Frozen collections of serum and plasma from studies of neurocognitive disorders, including measures of cognitive function, provide a resource for biomarker discovery in this arena 22 However, opportunistically collected samples rarely contain information regarding fed/fasted states, which can compromise “omics” analyses. Here, we took advantage of data and biospecimens from subjects in the Religious Order Study and Rush Memory and Aging Project (ROS/MAP) 23 , develop a predictive tool for the fasted/non-fasted state discrimination and stratify our biomarker discovery effort by the fasted state.…”
Section: Introductionmentioning
confidence: 99%
“…The EpETrEs are generally considered to be beneficial, having have vasodilatory and anti-inflammatory effects which are lost upon conversion to DiHETrEs [30]. Others have demonstrated an increase in DiHETrEs and other diol products of epoxide hydrolases in the serum and brains of individuals with vascular cognitive impairment compared with controls [31,32]. Our data indicated that epoxide 8,9-EpETrE and diol 14,15-DiHETrE levels were higher in the WM group compared to the LFLSM group and fasting group.…”
Section: Discussionmentioning
confidence: 46%
“…Linoleic acid is rstly metabolized to 12,13-EpOME by cytochrome P450 (CYP) epoxygenases, and followed by hydrolysis catalyzed by soluble epoxide hydrolases (sEHs) to form the diols 12,13-diHOME [83]. They have multiple pathological features, such as decreasing post-ischemic cardiac recovery, participating in the vascular cognitive impairment, increasing skeletal muscle fatty acid uptake and impeding immune tolerance in asthma child [31,[84][85][86]. And the 12,13-diHOME produced by sEH hydrolysis of 12,13-EpOME showed stronger cytotoxicity [83,87].…”
Section: Discussionmentioning
confidence: 99%